Diagnosis and management decision in delayed posterior mediastinal abscess secondary to thoracic esophageal perforation following accidental fish bone ingestion - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Mohamad Hashim, Shaharudin; K.S, Sathananthar; Kamarudin, Norie Azilah (2006)
Accidental swallowing of fish bone, which arrested in either the cervical or thoracic esophagus, is fairly common. However, the incidence of esophageal perforation due this fish bone is low. Delayed posterior mediastinal abscess as a result of the esophageal perforation is a rare manifestation and may leads to fatal outcome. Two cases of delayed formation of posterior mediastinal abscess following thoracic esophageal perforation due to accidental fish bone ingestion are described in this presentation. In both cases the sole clinical feature is interscapular back pain. In one of the cases the patient died because of the presentation was misdiagnosed hence delayed intervention. The clinical presentations, radiological findings and surgical management are discussed. Neck exploration and esophagoscopy as the surgical treatment for this problem are illustrated.